“La musicoterapia en el desarrollo de la coordinación motriz de los niños de Educación Inicial” - Chuquitarco Chicaiza, Grace Estefanía (2023)
The present investigation refers to the difficulties that children present concerning the development of motor coordination and the use of music therapy to strengthen this area. Therefore, the general objective was to diagnose the development of motor coordination and coordination use of music therapy in children of Initial Education of the Educational Unit "Victoria Vásconez Cuvi" of the Latacunga canton. The methodology is the qualitative approach, using the inductive method through the bibliographic design. Therefore, the techniques applied were the observation sheet addressed to the children and the interview with the teacher in charge of the level. Initial. According to the applied interview, it was determined that the teacher does not know about the usefulness of music therapy; for this reason, it was evident that she carries out activities without using this innovative resource, such as music, which has not allowed the children to continue strengthening motor coordination. Appropriately, on the other hand, it was evidenced that she uses strategies in which students are not motivated to participate in each proposed activity. Concerning the application of the observation sheet applied to children, it was possible to determine that they do not have a consistent development of motor coordination. It is evident that they still present certain complications when executing movements. For these reasons, it is considered essential to socialize teachers about the importance of motor coordination development and music therapy as a pedagogical tool that will benefit the development of children.